2016
DOI: 10.1177/0267659116683790
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 protects skeletal muscle from ischemia-reperfusion through the NF-kappa B pathway

Abstract: It seems that CoQ10 has inhibitory effects on NF-κB and TNF-α activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Therefore, it is not surprising that its depletion is associated with a greater propensity to develop immune inflammatory responses through the activation of inflammatory processes such as the nuclear factor-kappa-light-chain-enhancer of activated B cell's (NF-κB) gene expression [16]. Worthy to note, CoQ 10 is endowed with potent antioxidant action able to prevent free radical damage by the regulation of transcriptional pathways in addition to deactivation of inflammatory pathways [17].…”
Section: Organmentioning
confidence: 99%
“…Therefore, it is not surprising that its depletion is associated with a greater propensity to develop immune inflammatory responses through the activation of inflammatory processes such as the nuclear factor-kappa-light-chain-enhancer of activated B cell's (NF-κB) gene expression [16]. Worthy to note, CoQ 10 is endowed with potent antioxidant action able to prevent free radical damage by the regulation of transcriptional pathways in addition to deactivation of inflammatory pathways [17].…”
Section: Organmentioning
confidence: 99%
“…An anti-nociceptive effect of the CoQ10 has been studied in a rat model of knee OA and the mechanism of pain suppression was suggested to be caused by an anti-inflammation [ 39 ]. Previous in vivo study has also shown that CoQ10 pretreatment significantly inhibited TNF-α and NF-κβ activation during I/R of skeletal muscle [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…CoQ10 is a potent antioxidant frequently used in clinical practice. It potentially prevents the TQ-induced I/R injury because the CoQ, as part of mitochondrial ETC, regulates ATP and ROS synthesis [ 12 , 19 , 32 , 33 , 34 ]. In aging and chronic arthritis patients, endogenous CoQ10 levels have been shown to significantly decrease, thus inducing mitochondrial vulnerability to I/R processes [ 19 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…CoQ10 deficiency leads to mitochondrial disorders and cellular dysfunction especially in tissues with high energy requirements like skeletal muscles ( Romero-Moya et al, 2017 , Woodman et al, 2016 ). Boroujeni et al demonstrated the protective effect of CoQ10 in a model of HLI/R through suppression of NFκB and TNF-α ( Boroujeni et al, 2017 ). While the action of CoQ10 as an inhibitor of calcium influx and its favorable aspect on cellular damage is well documented ( Chang et al, 2012 , Okamoto et al, 1995 ), its effect on classical and non-classical RAS system is not revealed yet.…”
Section: Discussionmentioning
confidence: 99%